Lysozymuria in diabetes. Issue 6010 (13th March 1976) - Farr, M; Wardle, E N; Wilkinson, K
Abstract : A reversible lysozymuria indicative of proximal tubular damage to the kidney was found in three out of five patients with diabetic ketosis, and a persistent lysozymuria was found in many patients with diabetic nephropathy. There was no relation between lysozymuria and the degree of proteinuria, and lysozymuria was not due to urinary tract infection. The degree of lysozymuria could be used to assess the severity of diabetic nephropathy.